1995
DOI: 10.1007/bf02744840
|View full text |Cite
|
Sign up to set email alerts
|

X-ray analysis of different starch granules

Abstract: Crystal sizes and lattice distortion parameters for root, pulse and cereal starch granules have been determined using observed X-ray diffraction reflections by Fourier method. Enthalpy for the formation of the lattice in root, pulse and cereal starches has been estimated and compared. It is found that the crystal size is normally high in root starch compared to pulse and cereal starches.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

1999
1999
2021
2021

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 20 publications
0
8
0
Order By: Relevance
“…Briefly from XRD spectra, starches can be classified as A, B, and C types. 42 A-type starch has strong diffraction peaks at about 15 and 23°and an unresolved doublet at around 17 and 18°. B-type starch gives characteristic peak at 5.6°and a strong diffraction peak at 17.7°along with a few less intense peaks at 15, 20, 22, and 24°.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Briefly from XRD spectra, starches can be classified as A, B, and C types. 42 A-type starch has strong diffraction peaks at about 15 and 23°and an unresolved doublet at around 17 and 18°. B-type starch gives characteristic peak at 5.6°and a strong diffraction peak at 17.7°along with a few less intense peaks at 15, 20, 22, and 24°.…”
Section: Resultsmentioning
confidence: 99%
“…As inferred from Figure c, there is no significant change in the diffractograms of the two samples; however, the results suggest only a decrease in peak intensity after cross-linking the potato starch. Briefly from XRD spectra, starches can be classified as A, B, and C types . A-type starch has strong diffraction peaks at about 15 and 23° and an unresolved doublet at around 17 and 18°.…”
Section: Results and Discussionmentioning
confidence: 99%
“…[45] Crystalline natures of starches play a dominant role in determining swelling and enzymic behavior of starches. [46] The level of crystallinity and morphology significantly affects the properties of polymers. Polymers with high crystallinity have a higher glass transition temperature and have usually superior properties.…”
Section: Crystallinity Of Oat Starchmentioning
confidence: 99%
“…Joshi and Purnima [18] studied the mechanical properties and morphology of glass fiber, CaSiO 3 -reinforced PP hybrid composite, the results showed that the tensile, flexural, and impact properties of the composite were higher than those of the unfilled PP. Singh and his colleagues [19] evaluated the mechanical properties of polypropylene filled with CaSiO 3 and silicon rubber, and found that the notched impact strength, and flexural strength were enhanced, but the unnotched impact strength, tensile strength and flexural modulus were reduced.…”
Section: Introductionmentioning
confidence: 99%